Etching, engraving, and other intaglio printmaking techniques - Leaf, Ruth (New York : Dover Publications, 1984)
Introduces the tools, materials, equipment, and techniques used in etching, identifies common mistakes, and shows examples of various mediums
-- 1: General information -- Materials and equipment -- Tools -- Printing papers -- Presses -- Workshop -- 2: Etching techniques -- Formulas for grounds and inks -- Hard ground -- Soft ground -- Aquatint -- Sugar lift -- White ground -- Acids -- 3: Printing techniques -- Basic printing -- Double intaglio printing -- Color printing and embossing -- Viscosity method -- Viscosity and aquatint -- 4: Other mediums and methods -- Drypoint -- Engraving -- Collagraphs -- Tuilegraphs -- Blake transfer method
Reprint. Originally published: Intaglio printmaking techniques. New York : Watson-Guptill, 1976
Includes bibliographical references (page 229) and index
Keywords: Intaglio printing -- Technique